THE EFFICIENCY OF MOOCS IMPLEMENTATION IN TEACHING ENGLISH FOR PROFESSIONAL PURPOSES - Hаnnа M. Shalatska (Інформаційні технології і засоби навчання, 2018)
The article considers the way of integrating Massive Open Online Courses (MOOCs) into the educational process and determining their role in students’ motivation to learn a foreign language for professional purposes. The goal of the research is studying the efficiency of implementation of MOOCs as part of students’ independent work while learning a foreign language for professional purposes at the university. Considering the increasing need for education around the world, the role of MOOCs will become more important than ever before. Consequently, engaging students whose major is Information Technology in learning the integrating course could enhance their skill and knowledge of programming. The integration of MOOCs in the process of learning English for professional purposes will help to personalize learning environments and prepare future professionals. Research shows that the successful implementation of MOOCs can bring new opportunities to learners, such as increasing English proficiency level, developing critical thinking, decision-making, problem-solving and time management. We consider the scientific problem connected with the efficiency of using Internet resources and MOOCs, ways of using interactive online technologies in the traditional educational process, potential and identified new opportunities offered by e-learning. Our observations are also related to the problem of integrating MOOCs into the curriculum; adapting them to the thematic modules and different subjects. Research shows that successful integration of MOOCs in the process of learning a foreign language for professional purposes depends on a number of factors. Each stage of our research has been carefully considered in the article. This study shows the efficiency of MOOCs as additional resources in studying English for professional purposes and describes the use of information and communication technology of distance learning in the traditional educational process. In this article, we describe how this idea is being realized and can be adopted by universities willing to use benefits of MOOCs in teaching English for professional purposes.